2021
DOI: 10.3176/proc.2021.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Continuum mechanics and signals in nerves

Abstract: The review describes how ideas from the fields of physics and mathematics have influenced the studies on signal propagation in nerves, which has classically been related to electrophysiology and chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…In what follows, the ideas of DeLanda and Deleuze are used to characterise the modelling of signals in nerves proposed by Engelbrecht, Tamm and Peets [17,24]. It is demonstrated that such modelling corresponds to general philosophical ideas.…”
Section: Proceedings Of the Estonian Academy Ofmentioning
confidence: 95%
See 4 more Smart Citations
“…In what follows, the ideas of DeLanda and Deleuze are used to characterise the modelling of signals in nerves proposed by Engelbrecht, Tamm and Peets [17,24]. It is demonstrated that such modelling corresponds to general philosophical ideas.…”
Section: Proceedings Of the Estonian Academy Ofmentioning
confidence: 95%
“…It is demonstrated that such modelling corresponds to general philosophical ideas. In Section 2, the ideas of modelling [17] are briefly explained. Section 3 presents the ideas of DeLanda [8] based on Deleuze's philosophical notions, but reconstructs them within the framework of mathematical terminology.…”
Section: Proceedings Of the Estonian Academy Ofmentioning
confidence: 99%
See 3 more Smart Citations